Perbaikan Fenotipe Pertumbuhan Anak Babi Lokal Melalui Penyuntikan Gonadotropin Sebelum Induk Dikawinkan (IMPROVEMENT OF GROWTH PHENOTYPE OF LOCAL PIGLET BY GONADOTROPHIN INJECTION OF SOW PRIOR TO MATING) - Rayer, 1Debby Jacqueline Jochebed; ., Muladno; Maheshwari, Hera; Manalu, Wasmen (Jurnal Veteriner, 2016)
An experiment was designed to study the growth phenotypes of piglets born to sows injected withpregnant mare serum gonadotropin (PMSG) and human chorionic gonadotropin (hCG) prior to mating inorder to improve endogenous secretions of pregnant hormones during pregnancy. The experimental sowsused in this study were 10 local breed sows with body weight ranges of 30-40 kg. Before mating, estrouscycles of the experimental sows were synchronized by injecting 3.75 mg prostaglandin twice with 14 daysinterval. The experimental sows were then divided into two groups, each consisted of 5 sows. The firstgroup was injected with 200 IU PMSG and 100 IU hCG per sow at the same time with the secondprostaglandin injection (day 15th), while the second group was not injected with PMSG and hCG but it wasinjected with NaCl 0.95% as a control. After showing estrous behavior, the experimental sows were mixedwith selected boars for natural mating. The pregnant sows were maintained until farrowing and weaning. Variable measured were body weights and body lengths and leg heights of the piglets at birth andweaning. The results showed that injection of the sows with PMSG and hCG prior to the mating, increasedbirth weight by 76.92% and total birth weight of live piglets per sow by 265.6% as compared to control.Piglets born to sows injected with PMSG and hCG prior to mating had higher survival rate with adramatically decreased mortality and a higher pre-weaning growth rate that finally increased total weightof weaned pigs per sows dramatically by 107.44% (increased 2 times) as compared to control. It is concludedthat the growth phenotypes of local piglets could be improved by injecting the sows with gonadotropinbefore mating.
Keywords: superovulation; PMSG; hCG; birth weight; weaning weight; local pig